Beach Safety Practices and Preservation Management Strategies of the Selected Beach Resorts in Occidental Mindoro - John Paul; Aezanette C. Agkis; Ferdinand II E. Andres; John Aero P Caraan; Queenz Rhovie D Jualan; John Carlo R Rivadenera (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to understand the protective measures of safety management strategies for selected beach resorts in Occidental Mindoro. These include tourists’ risk perception, environmental considerations directly related to COVID-19, and safety management strategies designed to limit the risk of contagion on the beach. The study, therefore, identifies research prospects in these areas, additionally pointing out other questions, such as new carrying capacity methods, with the opportunity given by the arising situation of COVID-19 in the estimation of the assessment of beach safety practices and preservation management strategies. This research study will use quantitative descriptive correlation research. The researcher will gather data from eighty (80) respondents from the two (2) selected beach resorts in Occidental Mindoro, Maslud Cove and Paradise Beach.